EFFECTIVE STRATEGIES OF LEARNING ENGLISH - Kholmirzayeva Roziya Bakhtiyor kizi; Xursanmurodova Feruza Abdug'ani qizi; Aktamov Mukhriddin Uktam ugli; Boltaboyeva Ugiloy Bakhtiyor kizi (Bright Mind Publishing, 2026)
A system of effective and innovative strategies for learning and teaching foreign languages is outlined. Outlining such a system presupposes the use of both theoretical methods of analyzing a number of strategies for learning foreign languages. Human beings need to communicate on a daily basis for different purposes. They communicate to inform each other, to express their feelings, to influence others, to meet social expectations, to do business, to gain knowledge and skills, and so on. The factors that will lead to effective communication, a language, message and attitude play a big role for this purpose. A language is a tool of communication. Erlinda (2010) stated that both animal and human beings can communicate to each other. Languages are acquired or learned. English is one of those tools of Communication.
Keywords: System of and innovative strategies, theoretical methods, communicate, inform, daily basis, express their feelings, gain knowledge.